Isolated aphasic status epilepticus: CT perfusion, SPECT and EEG reveal neurovascular coupling and support the differential diagnosis. Issue 3 (19th July 2022) - Manganotti, Paolo; Furlanis, Giovanni; Cova, Maria Assunta; Olivo, Sasha; Dore, Franca; Sartori, Arianna; Naccarato, Marcello
Abstract: Objective . Among the clinical manifestations of stroke mimics, isolated aphasia is one of the most challenging due to its aetiopathogenic diagnosis. This short communication describes a specific perfusion and brain oscillatory pattern in a challenging case of prolonged isolated aphasia caused by status epilepticus(SE), jointly investigated by computed tomography (CT) perfusion, single‐photon emission computerized tomography (SPECT)/CT and EEG qualitative and quantitative analysis. Methods . We discuss the different patterns of perfusion neuroimaging and EEG between SE and ischaemic stroke or postictal (Todd's)‐related isolated aphasia, and propose these differences as a basis to support the differential diagnosis. Results . The pattern associated with SE was characterized by focal hyperperfusion on CT perfusion maps (the left mean transit time was shorter with >10% asymmetry, and left cerebral blood volume and cerebral blood flow increased or slightly altered, relative to the contralateral side) and SPECT (focal left temporal hyperperfusion), without any early ischaemic signs on non‐enhanced CT, while the EEG showed a predominant left hemispheric slow delta power. The aforementioned perfusion pattern contrasts with postictal epileptic Todd's phenomenon, which is characterized by hypoperfusion on CT perfusion (the mean transit time is prolonged and cerebral blood volume and cerebral blood flow are reduced, compared to the contralateral hemisphere) and SPECT (focal hypoperfusion), not restricted to the specific vascular territories. Significance . CT perfusion patterns may add valuable information to support the differential diagnosis of status epilepticus, rather than acute ischaemic stroke or postictal Todd's phenomenon, in cases with challenging symptoms of prolonged isolated aphasia.